Ethyl 2-[3-(3,5-Dinitrobenzoyl)thioureido]benzoate - Saeed, Sohail (International Union of Crystallography, 2011)
In the title compound, C(17)H(14)N(4)O(7)S, the dihedral angle between the two benzene rings is 9.04 (15)°. The centroid–centroid distance of 3.9825 (19) Å between nearly parallel benzene rings of adjacent molecules suggests the existence of π-π stacking. Intermolecular and intra-molecular N—H⋯O hydrogen bonding is present in the structure. The ethoxy group is disordered over two sets of sites with an occupancy ratio of 0.580 (15):0.420 (15). The crystal studied was an inversion twin.